Virtual Reality in Business Education: Systematic Literature Review - Juliana, Ari; Nurqamarani, Adisthy Shabrina; Fadila, Sarah; Rullinawati, Rullinawati; Aripin, Sofjan (Lembaran Ilmu Kependidikan, 2022)
Virtual reality has existed in the education field for quite some time and numerous research including systematic review papers have discussed virtual reality, particularly in STEM Education. However, there has been limited business education literature despite the increasing use of virtual reality in real-world business practices. Students need to keep pace with this technology to better prepare them as future graduates and/or entrepreneurs, and educators need to prepare and evaluate the use of virtual reality in improving students’ business skills. To gain a better understanding of the current state of virtual reality in business education and how effective it is in improving business skills, we have performed a systematic literature review of the use of virtual reality in business education within the last ten years. 118 abstracts’ screening and evaluation yield 10 selection studies included in the analysis. The result revealed that there has been limited use of a fully immersive type of virtual reality implemented in business education at higher education and most studies use a non-immersive type of virtual reality and belong to serious games categories. In addition, all articles agree that the uses of virtual reality in business education are effective in improving business skills.